Penggunaan Virtual lab. Circuit Wizard Untuk Simulasi Rangkaian High Pass Filter Pasif - Syifaul Fuada; Gita Alisrobia; Muntaha Hasanah; Meiliya Cahya Yustina; Dina Rahmawati (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
Passive High Pass Filter will be discussed in this paper; the filter itself is a circuit that determines the amount of a certain frequency to be streamed and will reject frequencies that are not suitable. Meanwhile, a passive filter is an electrical circuit that can block intervals at certain signal frequencies to filter incoming signals. The benefit of passive filters is that they can be used at higher frequencies because their dimensions are larger than active filters. Measurement of the voltage gain in the Passive High Pass Filter circuit using laboratory methods using a simulation approach with the Circuit Wizard simulator or directly. The research method consists of two experimental scenarios that aim to compare the signals generated from stage I to stage V. For the scenario I, the simulation is carried out using the Circuit Wizard simulator. The capacitor is one of the reactive components that will offer a variety of resistance to different frequency signals based on a High Pass RC Filter circuit with a capacitor that has a high value of resistance to low frequencies or resistance to high-frequency transmissions will be minimal. The capacitor feature makes it resistant to low-frequency or DC signals, so only high-frequency signals can travel through the capacitor and block the path of low-frequency impulses. The high pass filter can attenuate or maintain low frequencies below the cut-off frequency while passing high signal frequencies or passing signals above them.